Student Perspectives on Distance Second Language Learning - Sabri, Muhammad Mahrup Zainuddin (Yayasan Nurul Iman Muara Gading Mas, 2024)
Distance second language learning has emerged as a growing concern within higher education settings, particularly in light of challenges posed by a global pandemic such as COVID-19. This study endeavors to investigate students’ perspectives on distance second language learning and the factors impacting said perspectives. The research was carried out via a survey involving students enrolled in various English study programs across multiple universities in Indonesia. Data gathering methods comprised questionnaires and interviews, focusing on facets including social support, flexibility of scheduling, and integration of technology in the learning process. Findings from the study indicate that students generally hold favorable views towards distance second language learning, notwithstanding several obstacles such as technical issues and a preference for traditional face-to-face instruction. The implication of this research underscores the significance of fortifying social support structures and enhancing technology integration in distance learning to enhance student learning experiences.